2020
DOI: 10.5306/wjco.v11.i5.260
|View full text |Cite
|
Sign up to set email alerts
|

CITED2 and the modulation of the hypoxic response in cancer

Abstract: CITED2 (CBP/p300-interacting transactivator with Glu/Asp-rich C-terminal domain, 2) is a ubiquitously expressed protein exhibiting a high affinity for the CH1 domain of the transcriptional co-activators CBP/p300, for which it competes with hypoxia-inducible factors (HIFs). CITED2 is particularly efficient in the inhibition of HIF-1α-dependent transcription in different contexts, ranging from organ development and metabolic homeostasis to tissue regeneration and immunity, being also potentially involved in vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 128 publications
(152 reference statements)
0
11
0
Order By: Relevance
“…44,45 The negative role of endogenous CITED2 in HIF-1 activation has also been supported in vitro and in vivo, 41,45−47 revealing that CITED2-mediated inactivation of HIF-1 might be an important mode of action in cancer therapy. 48,49 Therefore, taking these properties of CITED2 into consideration, we hypothesized that CITED2 might be a starting point for designing potent peptide-based inhibitors of the HIF1α/p300 complex, providing a potential therapeutic strategy for cancer treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 The negative role of endogenous CITED2 in HIF-1 activation has also been supported in vitro and in vivo, 41,45−47 revealing that CITED2-mediated inactivation of HIF-1 might be an important mode of action in cancer therapy. 48,49 Therefore, taking these properties of CITED2 into consideration, we hypothesized that CITED2 might be a starting point for designing potent peptide-based inhibitors of the HIF1α/p300 complex, providing a potential therapeutic strategy for cancer treatment.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Besides the interaction between HIF1α and p300/CBP, several studies have revealed that CITED2 (also named p35srj or Mrg1) also acted as a negative regulator for HIF1 transcriptional activity by competing for binding to the same binding domain (CH1) of p300/CBP. The CITED2 was a strong competitor for binding to p300/CBP due to the partially overlapping binding sites with HIF1α, with a 33-fold tighter binding capacity to the CH1 domain of p300 compared to HIF1α. , The negative role of endogenous CITED2 in HIF-1 activation has also been supported in vitro and in vivo, , revealing that CITED2-mediated inactivation of HIF-1 might be an important mode of action in cancer therapy. , Therefore, taking these properties of CITED2 into consideration, we hypothesized that CITED2 might be a starting point for designing potent peptide-based inhibitors of the HIF1α/p300 complex, providing a potential therapeutic strategy for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Under hypoxia, CITED2 binds to CBP/P300 competitively with HIF-1α and forms CITED2-CBP/P300 complex. The complex inhibits the expression of VEGF gene encoding protein (25). In addition, it has been proposed that CITED2, as an anti-inflammatory cytokine, may play a role in angiogenesis inhibition through the PPAR pathway (26).…”
Section: Discussionmentioning
confidence: 99%
“…CITED2 (CBP/p300-interacting-transactivator-with-an ED-rich-tail 2) is a transcriptional regulator that co-activates or represses multiple transcription factors, including AP-2 ( Bamforth et al., 2001 ), HIF-1alpha ( Bhattacharya et al., 1999 ), PPAR-α ( Tien et al., 2004 ), SMAD2/3 ( Chou and Yang, 2006 ), and c-MYC ( Chou et al., 2012 ) to regulate fundamental cellular processes, such as proliferation, metabolism, differentiation, migration, and autophagy. Consistent with its ubiquitous expression and pleiotropic impact on diverse transcription factors, CITED2 is essential for embryonic development, including fetal liver hematopoiesis ( Bamforth et al., 2001 , 2004 ; Chen et al., 2007 ; Weninger et al., 2005 ; Withington et al., 2006 ; Yin et al., 2002 ), ESC biology ( Kranc et al., 2015 ; Li et al., 2012 ), adult tissue functions ( Kim et al., 2018 ; Lee et al., 2009 ; Liu et al., 2019 ), cellular proliferation ( Kranc et al., 2003 ), and cancer progression ( Fernandes et al., 2020 ). Thus, CITED2 is an important regulator of diverse molecular, cellular, and developmental processes.…”
Section: Introductionmentioning
confidence: 99%